Estimating the Disposable Income of Households at the Local Level - Sarioglo, V. H.; Leshenok, U. S. (Statistics of Ukraine, 2020)
The article is devoted to the problem of socio-economic indicators estimation of at the local level, first and foremost at the municipal and community level. Emphasis is made on approaches to the estimation of the households’ disposable income as a key indicator of the population’s standards of living, required for elaborating and implementing effective measures of socio-economic policy, implementing investment programs on the modernization of living quarters, objects of social infrastructure etc. The meaning of the term “disposable incomes” adopted in the official statistics of Ukraine, drawbacks of this definition and ways for its extension are illustrated. A broad description of studies focused on the assessment of population’s incomes at local level in various countries of the world is given. It is shown that the need for such problem solutions in the statistics caused the emergence of a separate theoretical field – small area statistics. A series of international and national projects aimed at the adaptation of elaborated theoretical and methodological approaches have been accomplished, in particular SAMPLE in EU countries and SAIPE in the U.S. Basically, results of the performed studies demonstrate a feasibility of the assessment of households’ incomes at local level with the acceptable degree of reliability. A review of the main data sources that can be used for estimation of households’ incomes at local level in Ukraine is made. It is stressed that data from administrative registers on salaries, pensions, stipends, social allowances, subsidies for utility services, taxes etc. have critical importance for the income assessment. Special sample surveys of households’ incomes and expenditures, performed at local or regional and national level, are highly significant for determining the patterns of correlations between incomes and principal characteristics of households, such as composition, region and locality of residence, type of dwelling, availability of movable and immovable property, land plots etc. It is substantiated that methods for quantitative estimation of disposable incomes should be given preference over expert assessment that tends to be used in the current conditions. Examples of the assessment of disposable incomes based on quite simple and comprehensible ratios are given. Areas of further studies focused on the estimation of population incomes at the local level are outlined.